Practical Guide for a Collaborative Osteomyelitis Service. Issue 4 (December 2015) - Suh, Gina; Kappagoda, Shanthi
Abstract : The treatment of osteomyelitis is challenging and best managed by a collaborative service involving both Orthopedic Surgery and Infectious Diseases. Here, we present a specialty service dedicated to the treatment of osteomyelitis in which a comprehensive, patient-centered approach is utilized. Key features are communication, colocation, dedicated staff, and education.